Program Tangguh Mental melalui Anger Management Training (PTM AMT) - Lilis Suryani; Dwi Retno Wati; Sukati Sarmin; Zeny Fatmawati (Health Care : Journal of Community Service, 2024)
The phenomenon of childbirth from year to year with the increasing caesarean section method and increasingly sophisticated caesarean section methods has made the scope of midwifery services narrower. One method that is currently being developed is the Eracs method of delivery by caesarean section. Where with this method many pregnant women are tempted by the word "painless", where many pregnant women with a fairly high percentage choose to deliver with this method without indications and without regard to the effects on the reproductive organs in the future. The aim is to carry out outreach to pregnant women about comfortable delivery in pregnant women with the "Gentle Birth" method. The results of this counseling are to increase pregnant women's knowledge about safe and comfortable childbirth, both normal and caesarean section. The counseling went well, in an orderly manner, and the pregnant women were very happy with the material provided, which can be seen from the enthusiasm of the mothers while participating in the counseling